Proposed Conceptual IoT-Based Patient Monitoring Sensor for Predicting and Controlling Dengue (International Journal of Communication Systems and Network Technologies, 2023)
Dengue is an epidemic-disease by mosquito-borne virus that spreads easily in geographically affected areas. Dengue outbreak management system has increasingly being developed in identifying and controlling the spread of dengue but with some limitation. The growing development of wearable Internet of Things (IoT), cloud computing, analytical approaches provide better alternative for dengue prediction and control. Previous literature collecting various parameters for analyzing dengue pattern. However, with the increasing number of analytical solution there is a need to investigate the high related parameters that should be use in analyzing and monitoring dengue outbreak before designing an IoT devices. Besides, there is a need for an alternative to ensure that early warning can be detected by monitoring the patient infected by the dengue, this paper aims to propose a conceptual IoT-based patient monitoring sensor for predicting and controlling dengue outbreak. Therefore, this paper provides a recent review of the latest methods and algorithms used to design wearable sensor for patient monitoring in dengue outbreak. Based on the review, this paper outlines the parameters that will be used in dengue for analyzing purposes. Finally, a conceptual IoT-based patient monitoring sensor were proposed comprising three different sensors to further work with analytical tools for dengue prediction pattern. The proposed conceptual design may help researcher to use the parameter identified for development of IoT sensor for dengue outbreak.
Keywords: Dengue Prediction; Internet of things; Patient Monitoring Sensor; Medical Informatics